Anxiety Is Associated With Uninvestigated and Functional Dyspepsia (Rome III Criteria) in a Swedish Population-Based Study - Aro, Pertti; Talley, Nicholas J.; Ronkainen, Jukka; Storskrubb, Tom; Vieth, Michael; Johansson, Sven Erik; Bolling-Sternevald, Elisabeth; Agréus, Lars (Gastroenterology, 2009)
Background & Aims: The Rome III criteria for functional dyspepsia have been changed to include 2 distinct syndromes: postprandial distress syndrome and epigastric pain syndrome. We investigated risk factors for functional dyspepsia among the functional dyspepsia subgroups defined by the Rome III criteria. Methods: We performed a cross-sectional population-based study in a primary care setting (the Kalixanda study). A random sample (n = 2860) of the adult population from 2 northern Swedish municipalities (n = 21,610) was surveyed using a validated postal questionnaire to assess gastrointestinal symptoms (response rate, 74.2%; n = 2122). A randomly selected subgroup (n = 1001) of responders was invited to undergo an esophagogastroduodenoscopy (participation rate, 73.3%) including biopsy specimen collection, Helicobacter pylori culture and serology, and symptom assessments. Results: Of the 1001 subjects examined by endoscopy, 202 (20.2%; 95% confidence interval [CI], 17.7-22.7) were classified as having uninvestigated dyspepsia and 157 (15.7%; 95% CI, 13.4-18.0) as having functional dyspepsia. Major anxiety (Hospital Anxiety and Depression Scale score ≥11) was associated with uninvestigated dyspepsia (odds ratio [OR], 3.01; 95% CI, 1.39-6.54), as was obesity (body mass index ≥30 kg/m2) (OR, 1.86; 95% CI, 1.15-3.01). Major anxiety was associated with functional dyspepsia and postprandial distress syndrome (OR of 2.56 [95% CI, 1.06-6.19] and 4.35 [95% CI, 1.81-10.46], respectively), as was use of nonsteroidal anti-inflammatory drugs (OR, 2.49 [95% CI, 1.29-4.78] and 2.75 [95% CI, 1.38-5.50], respectively). Depression was not associated with any dyspepsia group. Conclusions: Anxiety but not depression is linked to uninvestigated dyspepsia, functional dyspepsia, and postprandial distress syndrome but not to epigastric pain syndrome. © 2009 AGA Institute.
CRIS-Team Scopus Importer:2025-03-05